Chronic Active Arthritis Driven by Macrophages Without Involvement of T Cells: A Novel Experimental Model of Rheumatoid Arthritis. Issue 8 (20th June 2018) - Hagert, Cecilia; Sareila, Outi; Kelkka, Tiina; Nandakumar, Kutty Selva; Collin, Mattias; Xu, Bingze; Guérard, Simon; Bäcklund, Johan; Jalkanen, Sirpa; Holmdahl, Rikard
Abstract : Objective: To develop a new chronic rheumatoid arthritis model that is driven by the innate immune system. Methods: Injection of a cocktail of 4 monoclonal antibodies against type II collagen, followed on days 5 and 60 by intraperitoneal injections of mannan (from Saccharomyces cerevisiae ), was used to induce development of chronic arthritis in B10.Q mice. The role of the innate immune system as compared to the adaptive immune system in this arthritis model was investigated using genetically modified mouse strains. Results: A new model of chronic relapsing arthritis was characterized in B10.Q mice, in which a persistently active, chronic disease was found. This relapsing disease was driven by macrophages lacking the ability to mount a reactive oxygen species response against pathogens, and was associated with the classical/alternative pathway, but not the lectin pathway, of complement activation. The disease was independent of Fcγ receptor type III, and also independent of the activity of adaptive immune cells (B and T cells), indicating that the innate immune system, involving complement activation, could be the sole driver of chronicity. Conclusion: Chronic active arthritis can be driven innately by macrophages without the involvement of T and B cells in the adaptive immune system.